Sustainable smart cities in India : challenges and future perspectives - Sharma, Poonam, 1970-; Rajput, Swati (Urban book series., 2017)
This book presents fundamental and applied research aimed at the development of smart cities across India. Based on the exploration of an extensive array of multidisciplinary literature, this book discusses critical factors of smart city initiatives: management and organization, technology, governance, policy, people and communities, economy, infrastructure, and natural environment. These factors are broadly covered under the integrative framework of the book to examine the vision and challenges of smart city initiatives. The book suggests directions and agendas for smart city research and outlines practical implications for government professionals, students, research scholars and policy makers. A lot of work is happening on smart cities as it is an upcoming area of research and development. At international level, and even in India, the concept of smart cities concept is a hot topic at universities, research centers, ministries, transport departments, civic bodies, environment, energy and disaster organizations, town planners and policy makers. This book provides ideas and information to government officials, investors, experts and research students.